HOME AS THE PREFERRED PLACE OF DEATH: ARE THERE LIMITATIONS?. Issue 2 (1st June 2013) - Ganga-Krishnan, S; Wong, Lawrence; Song, Angeline; Nah, Tan Hui; Chung, Irwin
Abstract : Background: The HOME Programme provides home palliative services to patients with end-stage organ failure in Singapore. Aim: To study the reasons for patients who were not able to fulfil their wish to die at home. Method: A retrospective study was done based on historical data gathered from case notes of patients who had died during the period of April 2011 to September 2012. Results: A total of 143 patients had died. 102 patients (71%) had completed their ACP. Out of the 102 patients, 62 (61%) chose their homes as their preferred place of death. Out of the 62 patients who had chosen their homes as their preferred place of death, 41 patients (71%) died at home while 21 patients (29%) did not have their wish fulfilled. Discussion: Figure 1 Conclusion: Singapore has a multi-ethnic population. It's diverse cultural beliefs and perspectives towards palliative care and care-giving have an impact on end of life care decision-making. Currently, there is little research in this area. This paper has identified some causes to why patients were not able to fulfil their wish to die at home. It also navigates the way for future research to help patients die at home according to their wishes.